Trends in Unfortunate Accident Involving Technical Equipment Included a Full Technical Inspection Caused by External Causes in Poland 2006–2010 - Koziński, Jakub (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
As indicated by statistics number of technical devices is constantly growing. As the number of these devices grows naturally likelihood of an accident involving them. Therefore it would be appropriate insurance option from the above-mentioned events. Currently, the market does not give a single insurance against accidents involving technical equipment included a full technical inspection. The purpose of this paper is to construct a insurance involving equipment covered by a full technical inspection, together with the amount of premiums and other basic conditions of this instrument.